2018
DOI: 10.1002/jemt.23049
|View full text |Cite
|
Sign up to set email alerts
|

Multifunction interferometry using the electron mobility visibility and mean free path relationship

Abstract: A conventional Michelson interferometer is modified and used to form the various types of interferometers. The basic system consists of a conventional Michelson interferometer with silicon-graphene-gold embedded between layers on the ports. When light from the monochromatic source is input into the system via the input port (silicon waveguide), the change in optical path difference (OPD) of light traveling in the stacked layers introduces the change in the optical phase, which affects to the electron mean free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…According to Equation, the reflected light from a silicon end is affected by the incoming light from the input and the system, in which the chaotic signal can be generated when the suitable parameters and feedback are used, which are discussed below. Moreover, the feedback signal monitoring can be applied via the drop port output (mobility visibility), which can be obtained when the system is configured as the modified Michelson interferometer . The change in the electron mean free path within the gold layer affects the feedback energy and the switching output .…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Equation, the reflected light from a silicon end is affected by the incoming light from the input and the system, in which the chaotic signal can be generated when the suitable parameters and feedback are used, which are discussed below. Moreover, the feedback signal monitoring can be applied via the drop port output (mobility visibility), which can be obtained when the system is configured as the modified Michelson interferometer . The change in the electron mean free path within the gold layer affects the feedback energy and the switching output .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The electron drift velocity in the stacked gold layer is modulated by the plasmon waves from silicon to graphene, in which the driven electron mobility is obtained by the driven group velocity injected by the silicon‐graphene plasmonic waves, leads the increase in overall electron mobility within the gold layer. It affects the optical feedback signals, the through and drop port output signals, from which the drop port output is the function of the optical path difference (OPD, Δl ) of the Michelson interferometer, which can be seen in the form of the interference fringe (mobility visibility) by the change in the gold layer length, which relatively changes the electron mean free path . The relationship of the output fringe in terms of the electron mobility visibility can be written by …”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of over 100 years of use, interferometric approaches for measurement are still widely used as was seen in gravitational waves being experimentally confirmed through the results obtained from an interferometer [5]. The use of a Michelson interferometer with a plasmonic device has been recently reported by Nithiroth et al [9,10] with the use of other plasmonic interferometers found in recent literature [11][12][13][14][15][16][17]. There are many other interesting applications of plasmonic waves in the literature [18,19] and [20,21], where interesting plasmonic propagation and plasmonic graphene-Au nanostructure research has been reported.…”
Section: Introductionmentioning
confidence: 95%